2021
DOI: 10.1155/2021/5534241
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Metabolomic Analysis following Cecal Ligation and Puncture in Young and Aged Mice Reveals Age‐Associated Temporal Shifts in Nicotinamide and Histidine/Histamine Metabolic Pathways

Abstract: Introduction. Aged individuals are at higher risk for morbidity and mortality following acute stressors than similarly stressed young people. Evaluation of age-associated metabolic changes could lead to the identification of specific therapeutic targets to improve outcomes from acute stressors, such as infections, in the elderly. We thus compared the plasma metabolomes of both young and old mice following cecal ligation and puncture (CLP), an accepted model of acute infection and stress. Methods. Young (9-17 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…This encourages mining sepsis-exclusive changes in metabolites as biomarkers distinct from normal fasting outcomes. For instance, although α linolenic acid and linoleic acid show no significant alterations in response to 48 hours of fasting in mice (57), the present study highlights accumulation of metabolites involved in α linolenic acid and linoleic acid metabolism as a top enriched pathway in septic mice, concordant with results in age-matched (young) mice 12 hours after CLP in a recent study (58). Stephen et al conducted NMR-based metabolomics in serum of CLP mice at 24 hours and used a sham with 24 hours fasting as a control.…”
Section: Discussionsupporting
confidence: 92%
“…This encourages mining sepsis-exclusive changes in metabolites as biomarkers distinct from normal fasting outcomes. For instance, although α linolenic acid and linoleic acid show no significant alterations in response to 48 hours of fasting in mice (57), the present study highlights accumulation of metabolites involved in α linolenic acid and linoleic acid metabolism as a top enriched pathway in septic mice, concordant with results in age-matched (young) mice 12 hours after CLP in a recent study (58). Stephen et al conducted NMR-based metabolomics in serum of CLP mice at 24 hours and used a sham with 24 hours fasting as a control.…”
Section: Discussionsupporting
confidence: 92%
“…They could synthesize anserine, 5-formimidoyltetrahydrofolic acid, 4-fumarylacetoacetate, 5,6,7,8-tetrahydrobiopterin, and S -adenosylmethioninaminium. These compounds have the functions of antioxidant, anti-anemia, anti-nervous degeneration, anti-metabolism disorder, and maintenance of DNA methylation. These synthetic products might play a vital role in the anti-malarial properties of SA.…”
Section: Discussionmentioning
confidence: 99%
“…B6J mice had high levels of acylcarnitines at week 6 and high levels of phenylalanine, ornithine, and tyrosine at week 14 (9). In addition, the histidine/histamine pathway (10), tryptophan, purine, amino acid and nicotinamide metabolism (11), glycine, serine and threonine metabolism, glyoxylic acid, and dicarboxylic acid metabolism pathways in mice are significantly correlated with age (12)(13)(14)(15). In a urine metabonomic analysis of healthy children, the researchers found that these significantly age-related metabolites in infancy were amino acid and fatty acid metabolic pathways and carbohydrate metabolism (16).…”
Section: Introductionmentioning
confidence: 99%